ANALISIS FAKTOR-FAKTOR KEMISKINAN DI KABUPATEN/KOTA DAERAH ISTIMEWA YOGYAKARTA - Ayu Salsabilla (2021)
The problem of poverty in 5 Regencies/Cities of the Special Region of Yogyakarta when measured by the percentage of poor people (Head Count Index) has decreased but tends to be slow in 2014-2019 and this problem is a challenge for the government because the poverty rate is still high in the first rank in Java and above the national poverty rate. This happens because the number of people who experience an increase every year will have an impact on reducing the number of household savings, the increase in HDI tends to be very slow and there are still areas that are lagging behind the national average, the minimum wage is relatively low so that people find it difficult to meet their needs. live a normal life and the number of employment in DIY is moving very slowly because of the limited number of jobs in DIY. This study uses panel data regression analysis technique with the data used is secondary data obtained from the Central Statistics Agency. The results obtained indicate that the population, minimum wage, employment have an effect while HDI has no effect on poverty. Suggestions for further researchers are to add other variables that affect poverty so as to produce more useful research and the difference in the results of the independent variables used must be further proven in theory.